A fiber dispersion foaming agent for foam molding and its preparation method and application

By using a composite foaming agent of fibrous nanoparticles and surfactant in the foam molding process, the problems of foam prone to burst and fiber agglomeration are solved, and more stable foam molding and more uniform paper-forming quality are achieved.

CN116905277BActive Publication Date: 2025-04-04SOUTH CHINA UNIV OF TECH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202310808093.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-07-04
Publication Date
2025-04-04
Estimated Expiration
2043-07-04

AI Technical Summary

Technical Problem

The foam is prone to burst during foam forming, resulting in fiber agglomeration and affecting the uniformity of paper formation.

Method used

A special fiber dispersion foaming agent for foam forming is adopted, which includes nanoparticles, surfactants and water, and enhances the stability of the foam and prevents fiber agglomeration through the adsorption and steric hindrance of the fibrous nanoparticles.

Benefits of technology

It significantly improves the stability of the foam and the uniformity of the paper forming process, extends the half-life of the foam, improves the dispersion state of the fiber, and improves the tensile stress and surface quality of the paper forming process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116905277B_ABST
    Figure CN116905277B_ABST
Patent Text Reader

Abstract

The invention discloses a fiber dispersing foaming agent for foam molding, a preparation method and application thereof, and belongs to the field of papermaking technology. A fiber dispersing foaming agent for foam molding, comprising nanoparticles, a surfactant and water, wherein the weight ratio of the nanoparticles, the surfactant and the water is (0.01-0.10): (0.2-8): (100-300). The invention innovatively combines the adsorption behavior of fibrous nanoparticles on substances and the amphiphilicity formed by the surfactant, optimizes the foaming process, exerts the synergistic effect of the fibrous nanoparticles and the surfactant, and prepares a foam slurry with high stability. At the same time, with the help of the steric hindrance effect generated by the adsorption of fibrous nanoparticles on the fiber surface, the fiber re-agglomeration is hindered, the dispersion effect of the fiber in the foam slurry is enhanced, and paper with good uniformity is obtained. The invention is suitable for industrial continuous production and provides a theoretical basis and technical support for the development of foam molding process technology.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of papermaking, and in particular to a fiber dispersing foaming agent special for foam molding, and a preparation method and application thereof. Background Art

[0002] Foam molding is a new molding method that uses water-based foam instead of water as a fiber dispersion medium. It has obvious advantages in improving the fiber dispersion effect. The foam formed by foaming is a thermodynamically unstable system. As time goes by, the foam will gradually break. Whether it is to maintain the foam state or eliminate the foam, or to meet the requirements for paper uniformity and other structural characteristics, it is particularly important to control the stability of the foam. The suitable foam half-life for foam molding is between several hundred seconds. A half-life that is too long or too short does not meet the actual paper requirements. If the foam is too stable (the half-life is too long), it will seriously affect the subsequent defoaming and dehydration, affecting the progress of the project; if the foam is easy to break (the half-life is too short), the fibers will re-agglomerate, resulting in poor uniformity of the final paper.

[0003] Surfactants such as multi-branched isomeric tridecanol polyoxyethylene ether, dodecyl bishydroxyethyl methyl amine oxide and dodecyl dimethyl amine oxide are more suitable surfactants in foam forming processes, but the foam formed by these surfactants is unstable, and the upper foam is very likely to break during vacuum filtration, resulting in fiber flocculation, resulting in poor paper performance. For example, in the patent CN 114717870 A, dodecyl dimethyl amine oxide is used as a surfactant, quartz fiber (6mm) is added, and a fiber structure preform is prepared by a foam forming preparation method. The uniformity of the obtained product is within the range of 93-187. Although compared with the wet forming process, CN 114717870 A improves the uniformity of the product, the fiber still has a large area of ​​agglomeration on the surface of the product, and the product uniformity has a large room for improvement. Therefore, in order to solve the problems of easy rupture of foam and uniformity of paper in the foam forming process, it is urgent to develop a special fiber dispersing foaming agent for foam forming, which can keep the foam stable while evenly dispersing the fibers, so that they are in a good and stable dispersed state, and then vacuumize and dry to obtain paper with good uniformity. Summary of the invention

[0004] The present invention aims at the problems of easy foam breakage and paper uniformity in the foam forming process, and the primary purpose of the present invention is to provide a fiber dispersing foaming agent special for foam forming.

[0005] Another object of the present invention is to provide a method for preparing a fiber-dispersed foaming agent specifically for foam molding.

[0006] Another object of the present invention is to provide the application of the above-mentioned fiber-dispersing foaming agent specifically for foam molding, utilizing the adsorption behavior of fibrous nanoparticles on substances and the amphiphilicity of the surfactant itself to enhance the stability of the foam; at the same time, with the help of the steric hindrance effect produced by the adsorption of fibrous nanoparticles on the fiber surface, the fibers are prevented from re-agglomerating to obtain paper with good uniformity.

[0007] To achieve the above object, the technical solution of the present invention is as follows:

[0008] A fiber dispersing foaming agent for foam molding, the fiber dispersing foaming agent comprising nanoparticles, a surfactant and water;

[0009] The weight ratio of nanoparticles, surfactant and water is (0.01-0.10):(0.2-8):(100-300).

[0010] Preferably, the weight ratio of nanoparticles, surfactant and water in the fiber dispersion foaming agent is (0.02-0.08):(0.4-6):200.

[0011] Preferably, the nanoparticles are at least one of carboxylated cellulose nanofiber whiskers, carboxylated cellulose nanofibers, sulfonated cellulose nanofiber whiskers and cellulose nanofiber whiskers, more preferably carboxylated cellulose nanofibers;

[0012] The surfactant is at least one of alkyl polyglucoside 0810, dodecyltrimethylammonium bromide, dodecyldimethylamine oxide and cocamidopropyl betaine, and more preferably dodecyldimethylamine oxide.

[0013] Preferably, the nanoparticles have a diameter of 4-100 nm and a length of 0.2-5 μm.

[0014] The preparation method of the above-mentioned fiber-dispersed foaming agent for foam molding comprises the following steps:

[0015] (1) preparing a nanoparticle dispersion: adding nanoparticles into water according to the formula, stirring, and ultrasonicating to obtain a nanoparticle dispersion;

[0016] (2) Preparation of fiber dispersing foaming agent: adding a surfactant to the dispersion prepared in step (1), stirring at a low speed, and ultrasonicating to obtain a fiber dispersing foaming agent.

[0017] Preferably, the stirring in step (1) is preliminary stirring followed by stirring at 20000-30000 rpm for 10-20 min;

[0018] The ultrasonic time in steps (1) and (2) is 5-10 minutes.

[0019] The above-mentioned fiber dispersing foaming agent specially used for foam molding is used in the preparation of paper by foam molding process.

[0020] A method for preparing paper using the above-mentioned fiber-dispersed foaming agent for foam molding comprises the following steps:

[0021] (1) Add 3-12 parts by weight of inorganic fiber, polyester fiber, and thickener to 700-800 parts by weight of water, and disintegrate for 90-180 seconds. After the disintegration, add 200-300 parts by weight of a fiber dispersion foaming agent for foam molding, and pre-mix and stir with a three-layer three-blade stirring paddle to obtain a foam slurry;

[0022] (2) Pour the foam slurry into a forming funnel, filter to obtain a wet paper web, and dry to obtain finished paper.

[0023] Preferably, the inorganic fiber is at least one of quartz fiber and alumina fiber, and has a length of 3-30 mm;

[0024] The polyester fiber is at least one of PET fiber, PBT fiber and PTT fiber, and the amount used is 2-12wt.% of the weight of the absolute dry inorganic fiber;

[0025] The thickener is at least one of sodium alginate, sodium carboxymethyl cellulose, polyethylene oxide and sodium polyacrylate, and the amount used is 0.5-4.0wt.% of the absolute dry inorganic fiber weight.

[0026] The stirring in step (1) is 1400-1500 rpm for 15-20 min.

[0027] A finished paper is prepared by the above method.

[0028] Preferably, the paper weight is 195-780 g / cm 2

[0029] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0030] (1) The raw materials used for the foaming agent prepared by the present invention are environmentally friendly and pollution-free, and have a wide range of sources. It is a green and environmentally friendly material. Therefore, the synthesized foaming agent is environmentally friendly and safe, and meets the trend requirements of modern environmental protection.

[0031] (2) The foam stability generated by the mixed system of fibrous nanoparticles and surfactants prepared in the present invention is significantly stronger than that generated by a single surfactant system, and the comprehensive index is large. The half-life of the foam slurry with 0.04 weight parts of fibrous nanoparticles is 267s, the foam air content is 64.38%, and the foam volume is 2996.72cm 3 .

[0032] The fibrous nanoparticles of the present invention are arranged in a bundle-like extended chain structure, and several or dozens of bundle structures can be formed under the same unit, which can be better adsorbed on the bubble / fiber surface. At the same time, the surface of the fibrous nanoparticles contains carboxyl groups, which will form an electrostatic attraction with the ammonium oxide group in the surfactant. Therefore, the fibrous nanoparticles will be adsorbed on the liquid film and arranged closely, and a resistance effect will be generated on the hydrodynamic flow in the liquid film, thereby slowing down the drainage of the liquid film. In addition, due to the dense arrangement of the fibrous nanoparticles in the liquid film, the contact area between the gas and the liquid is reduced, and the disproportionation effect of the foam is also suppressed to a certain extent. The present invention gives full play to the synergistic effect of the fibrous nanoparticles and the surfactant, so that the foam reaches the optimal required state for molding.

[0033] (3) Fibrous nanoparticles can be used as dispersants. They can help disperse inorganic fibers and improve the fiber flocculation state through the steric hindrance effect caused by the adsorption of fibrous nanoparticles on the fiber surface. In addition, the fibrous nanoparticles have a large specific surface area, which increases the contact points with the fibers, allowing the fibers to be evenly distributed in various parts of the foam, effectively improving the uniformity of the finished paper. The uniformity of the finished paper surface increased by 14.2%-17.9%, and the uniformity of the top surface increased by 2.7%-23.1%. In addition, the tensile stress of the finished paper increased by 82.2%-568.9%.

[0034] (4) The foaming agent preparation process is simple to operate and is suitable for industrial continuous production. It provides new ideas for the green preparation and production of foam molding process products, and also provides a theoretical basis and technical support for the development of foam molding process technology. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 It is a visual diagram of foam slurry;

[0036] Figure 2 The diagrams of blowing agent half-life, foam air content and foam volume under different process conditions;

[0037] Figure 3 It is the comprehensive index diagram of foaming agent under different process conditions;

[0038] Figure 4 The paper uniformity diagrams under different process conditions are as follows: A: no nanoparticles added (Example 5); B: 0.02 parts of nanoparticles (Example 1); C: 0.04 parts of nanoparticles (Example 2); D: 0.06 parts of nanoparticles (Example 3); E: 0.08 parts of nanoparticles (Example 4);

[0039] Figure 5 This is the tensile stress diagram of finished paper under different process conditions;

[0040] Figure 6 This is the laser confocal image of the foam;

[0041] Figure 7 The graphs are the half-life, foam air content, and foam volume of different fibrous nanoparticle foaming agents (the dosage is all 0.02 parts);

[0042] Figure 8 This is a graph of the comprehensive foam index of different fibrous nanoparticle foaming agents (the dosage is 0.02 parts). DETAILED DESCRIPTION

[0043] In order to further understand the present invention, the embodiments of the present invention will be further described in detail below in combination with examples and comparative examples, but the embodiments of the present invention are not limited thereto. For process parameters not particularly noted, conventional techniques can be referred to.

[0044] The three-layer three-blade stirring paddle used in the embodiment has been disclosed in patent CN114717870A.

[0045] Example 1

[0046] (1) preparing a fibrous nanoparticle dispersion: adding 0.02 parts by weight of carboxylated cellulose nanofibers (diameter: 6-10 nm, length: 2-3 μm) to 200 parts by weight of deionized water, first stirring with a glass rod, stirring at 20,000 rpm for 10 min, and then ultrasonicating for 10 min to obtain a fibrous nanoparticle dispersion;

[0047] (2) preparing a fiber dispersing foaming agent: adding 6 parts by weight of dodecyl dimethyl amine oxide to the dispersion prepared in step (1), stirring at 500 rpm for 5 minutes, and ultrasonicating for 5 minutes to obtain a fiber dispersing foaming agent;

[0048] (3) Prepare the foam slurry system: add 3 parts by weight of quartz fiber (diameter: 6-12nm, length: 6-8μm), 8wt.% PET fiber (to the absolute dry inorganic fiber weight), 1.0wt.% polyethylene oxide (to the absolute dry inorganic fiber weight) to 800 parts by weight of tap water, and decompose for 90 seconds. After decomposition, add all the fiber dispersion foaming agent, pre-mix with a three-layer three-blade stirring paddle, and then stir at 1400rpm for 15 minutes to obtain a foam slurry;

[0049] (4) Preparation of paper: Pour the foam slurry obtained in step (3) into a forming funnel, filter and obtain a wet paper web. Place the wet paper web in an oven set at 165°C and dry for 2 hours to obtain a paper web with a weight of 195 g / cm 2 of paper.

[0050] Example 2

[0051] (1) preparing a fibrous nanoparticle dispersion: adding 0.04 parts by weight of carboxylated cellulose nanofibers (diameter: 6-10 nm, length: 2-3 μm) to 200 parts by weight of deionized water, stirring the mixture with a glass rod, stirring the mixture at 20,000 rpm for 10 min, and then ultrasonicating the mixture for 10 min to obtain a fibrous nanoparticle dispersion;

[0052] (2) preparing a fiber dispersing foaming agent: adding 6 parts by weight of dodecyl dimethyl amine oxide to the dispersion prepared in step (1), stirring at 500 rpm for 5 minutes, and ultrasonicating for 5 minutes to obtain a fiber dispersing foaming agent;

[0053] (3) Prepare the foam slurry system: add 3 parts by weight of quartz fiber (diameter: 6-12nm, length: 6-8μm), 8wt.% PET fiber (to the absolute dry inorganic fiber weight), 1.0wt.% polyethylene oxide (to the absolute dry inorganic fiber weight) to 800 parts by weight of tap water, and decompose for 90 seconds. After decomposition, add all the fiber dispersion foaming agent, pre-mix with a three-layer three-blade stirring paddle, and then stir at 1400rpm for 15 minutes to obtain a foam slurry;

[0054] (4) Preparation of paper: Pour the foam slurry obtained in step (3) into a forming funnel, filter and obtain a wet paper web. Place the wet paper web in an oven set at 165°C and dry for 2 hours to obtain a paper web with a weight of 195 g / cm 2 of paper.

[0055] Example 3

[0056] (1) preparing a fibrous nanoparticle dispersion: adding 0.06 parts by weight of carboxylated cellulose nanofibers (diameter: 6-10 nm, length: 2-3 μm) to 200 parts by weight of deionized water, first stirring with a glass rod, stirring at 20,000 rpm for 10 min, and then ultrasonicating for 10 min to obtain a fibrous nanoparticle dispersion;

[0057] (2) preparing a fiber dispersing foaming agent: adding 6 parts by weight of dodecyl dimethyl amine oxide to the dispersion prepared in step (1), stirring at 500 rpm for 5 minutes, and ultrasonicating for 5 minutes to obtain a fiber dispersing foaming agent;

[0058] (3) Prepare the foam slurry system: add 3 parts by weight of quartz fiber (diameter: 6-12nm, length: 6-8μm), 8wt.% PET fiber (to the absolute dry inorganic fiber weight), 1.0wt.% polyethylene oxide (to the absolute dry inorganic fiber weight) to 800 parts by weight of tap water, and decompose for 90 seconds. After decomposition, add all the fiber dispersion foaming agent, pre-mix with a three-layer three-blade stirring paddle, and then stir at 1400rpm for 15 minutes to obtain a foam slurry;

[0059] (4) Preparation of paper: Pour the foam slurry obtained in step (3) into a forming funnel, filter and obtain a wet paper web. Place the wet paper web in an oven set at 165°C and dry for 2 hours to obtain a paper web with a weight of 195 g / cm 2 of paper.

[0060] Example 4

[0061] (1) preparing a fibrous nanoparticle dispersion: adding 0.08 parts by weight of carboxylated cellulose nanofibers (diameter: 6-10 nm, length: 2-3 μm) to 200 parts by weight of deionized water, first stirring with a glass rod, stirring at 20,000 rpm for 10 min, and then ultrasonicating for 10 min to obtain a fibrous nanoparticle dispersion;

[0062] (2) preparing a fiber dispersing foaming agent: adding 6 parts by weight of dodecyl dimethyl amine oxide to the dispersion prepared in step (1), stirring at 500 rpm for 5 minutes, and ultrasonicating for 5 minutes to obtain a fiber dispersing foaming agent;

[0063] (3) Preparation of foam slurry system: Add 3 parts by weight of quartz fiber, 8 wt.% PET fiber (to the absolute dry inorganic fiber weight), and 1.0 wt.% polyethylene oxide (to the absolute dry inorganic fiber weight) to 800 parts by weight of tap water, and deagglomerate for 90 seconds. After deagglomeration, add all fiber dispersing foaming agents, pre-mix with a three-layer three-blade stirring paddle, and then stir at 1400 rpm for 15 minutes to obtain foam slurry;

[0064] (4) Preparation of paper: Pour the foam slurry obtained in step (3) into a forming funnel, filter and obtain a wet paper web. Place the wet paper web in an oven set at 165°C and dry for 2 hours to obtain a paper web with a weight of 195 g / cm 2 of paper.

[0065] Example 5

[0066] (1) preparing a fiber dispersing foaming agent: adding 6 parts by weight of dodecyl dimethyl amine oxide to 200 parts by weight of deionized water, stirring at 500 rpm for 5 minutes, and ultrasonicating for 5 minutes to obtain a fiber dispersing foaming agent free of fibrous nanoparticles;

[0067] (2) Preparation of foam slurry system: Add 3 parts by weight of quartz fiber (diameter: 6-12 nm, length: 6-8 μm), 8 wt.% PET fiber (to the absolute dry inorganic fiber weight), 1.0 wt.% polyethylene oxide (to the absolute dry inorganic fiber weight) to 800 parts by weight of tap water, and decompose for 90 seconds. After decomposition, add all fiber dispersing foaming agent, pre-mix with a three-layer three-blade stirring paddle, and then stir at 1400 rpm for 15 minutes to obtain foam slurry.

[0068] (3) Preparation of paper: Pour the foam slurry obtained in step (2) into a forming funnel, filter and obtain a wet paper web. Place the wet paper web in an oven set at 165°C and dry for 2 hours to obtain a paper web with a weight of 195 g / cm 2 of paper.

[0069] The result is as follows:

[0070] Figure 2 The figure shows the half-life of the foaming agent, the foam air content, and the foam volume under different process conditions. It can be seen from the figure that when only the surfactant is added, the half-life of the foam slurry is 116s, the foam air content is 65.07%, and the foam volume is 2945.27cm 3 When 0.02 parts by weight of fibrous nanoparticles + surfactant were added, the half-life of the foam slurry was 209s, the foam air content was 64.40%, and the foam volume was 2996.73cm 3 When 0.04 parts by weight of fibrous nanoparticles + surfactant were added, the half-life of the foam slurry was 267s, the foam air content was 64.38%, and the foam volume was 2996.72cm 3 When 0.06 parts by weight of fibrous nanoparticles + surfactant were added, the half-life of the foam slurry was 302s, the foam air content was 62.36%, and the foam volume was 2887.39cm 3 When 0.08 parts by weight of fibrous nanoparticles + surfactant were added, the half-life of the foam slurry was 392s, the foam air content was 62.39%, and the foam volume was 2855.24cm 3 .Depend on Figure 2 It can be seen that when only surfactant is added, the half-life is only 116s, which is much lower than the half-life of the foam generated by the combination of fibrous nanoparticles and surfactants. The half-life increases with the increase of the amount of fibrous nanoparticles, indicating that the combination of fibrous nanoparticles and surfactants can keep the foam in a uniform and stable state; the foam air content of the foam slurry decreases with the increase of the amount of fibrous nanoparticles. This may be because the addition of fibrous nanoparticles increases the viscosity of the slurry. As the amount of particles continues to increase, the viscosity gradually increases, a small amount of gas cannot form bubbles in the slurry, and the foam air content decreases; the foam volume of the foam slurry first increases and then decreases rapidly with the increase of the amount of fibrous nanoparticles. This may be because an appropriate amount of particles will adsorb with part of the surfactant, the hydrophobicity is enhanced, more fibrous nanoparticles cover the gas-liquid interface, and the low-energy gas-solid interface replaces the high-energy gas-liquid interface, the free energy of the slurry system is reduced, the bubble stability is enhanced, the foam volume increases, and the subsequent addition of too many fibrous nanoparticles increases the viscosity, thereby reducing the foam volume.

[0071] Figure 3It is the comprehensive index diagram of foaming agent under different process conditions. Figure 3 It can be seen that the comprehensive foam index increases with the increase in the amount of fibrous nanoparticles used, which shows that the combination of fibrous nanoparticles and surfactants is beneficial to foam stability and can greatly improve foam stability. Figure 2 The half-life analysis results were consistent.

[0072] Figure 4 The following are the paper uniformity diagrams under different process conditions. The smaller the uniformity, the better the paper uniformity. A is the paper with only surfactant added, with a web uniformity of 61.9 and a top surface uniformity of 69.8; B is the paper with 0.02 parts by weight of fibrous nanoparticles + surfactant, with a web uniformity of 65.9 and a top surface uniformity of 67.9; C is the paper with 0.04 parts by weight of fibrous nanoparticles + surfactant, with a web uniformity of 53.1 and a top surface uniformity of 57.3; D is the paper with 0.06 parts by weight of fibrous nanoparticles + surfactant, with a web uniformity of 51.6 and a top surface uniformity of 54.8; E is the paper with 0.08 parts by weight of fibrous nanoparticles + surfactant, with a web uniformity of 51.0 and a top surface uniformity of 53.7. As can be seen from the figure, the uniformity of the paper prepared by the composite foaming agent is significantly better than that of the single foaming system. The uniformity of the paper decreases with the increase of the amount of fibrous nanoparticles used, and the uniformity is improved. This may be because: (1) the presence of fibrous nanoparticles prolongs the foam half-life and hinders the possibility of fiber agglomeration due to foam rupture; (2) the fibrous nanoparticles can be used as dispersants, which helps to disperse the fibers even when used in a small amount.

[0073] Figure 5 The following is a graph of the tensile stress of finished paper under different process conditions. The greater the tensile stress, the better the tensile strength (tested using the INSTRON 3300 series mechanical testing system, with a sample width of 15mm and a fixture height of 15mm). As can be seen from the figure, when only a surfactant is added, the tensile stress is 0.90Mpa; when 0.02 parts by weight of fibrous nanoparticles + surfactants are added, the tensile stress is 1.64Mpa; when 0.04 parts by weight of fibrous nanoparticles + surfactants are added, the tensile stress is 4.80Mpa; when 0.06 parts by weight of fibrous nanoparticles + surfactants are added, the tensile stress is 5.24Mpa; when 0.08 parts by weight of fibrous nanoparticles + surfactants are added, the tensile stress is 6.02Mpa, and the tensile stress is increased by 82.2%-568.9%. As can be seen from the figure, the tensile stress of the finished paper prepared with a compound foaming agent is significantly better than that of a single foaming system. The tensile stress of the paper increases with the increase in the amount of fibrous nanoparticles used, and the tensile strength is enhanced.

[0074] Figure 6This is the appearance of foam under a laser confocal microscope. With fibrous nanoparticles as the test object, a fluorescent view of fibrous nanoparticles adsorbed on the surface of bubbles was obtained under a green fluorescent probe. It can be clearly seen from the figure that the fibrous nanoparticles are evenly adsorbed on the surface of the bubbles, reducing the contact area between gas and liquid. The dense particle film formed by the fibrous nanoparticles can inhibit the aggregation and disproportionation of bubbles. At the same time, the irregular arrangement of nanoparticles at the gas-liquid interface also prolongs the drainage time of the liquid film, producing a stronger foam stabilization effect.

[0075] Comparative Example 1

[0076] (1) preparing a fibrous nanoparticle dispersion: adding 0.02 parts by weight of sulfonated cellulose nanowhiskers (diameter: 10-20 nm, length: 100-300 nm) to 200 parts by weight of deionized water, first stirring with a glass rod, stirring at 20,000 rpm for 10 min, and then ultrasonicating for 10 min to obtain a fibrous nanoparticle dispersion;

[0077] (2) Preparation of fiber dispersing foaming agent: Add 6 parts by weight of dodecyl dimethyl amine oxide to the dispersion prepared in step (1), stir at 500 rpm for 5 minutes, and ultrasonicate for 5 minutes to obtain a fiber dispersing foaming agent.

[0078] Comparative Example 2

[0079] (1) preparing a fibrous nanoparticle dispersion: adding 0.02 parts by weight of cellulose nanofiber whiskers (diameter: 10-20 nm, length: 200-400 nm) to 200 parts by weight of deionized water, stirring the mixture with a glass rod, stirring at 20,000 rpm for 10 min, and then ultrasonicating the mixture for 10 min to obtain a fibrous nanoparticle dispersion;

[0080] (2) Preparation of fiber dispersing foaming agent: Add 6 parts by weight of dodecyl dimethyl amine oxide to the dispersion prepared in step (1), stir at 500 rpm for 5 minutes, and ultrasonicate for 5 minutes to obtain a fiber dispersing foaming agent.

[0081] The result is as follows:

[0082] Figure 7 The figure shows the half-life, foam air content, and foam volume of different fibrous nanoparticle foaming agents. It can be seen from the figure that when only surfactant is added, the half-life of the foam slurry is 116s, the foam air content is 65.07%, and the foam volume is 2945.27cm 3 When 0.02 parts by weight of sulfonated cellulose nanowhiskers were added, the half-life of the foam slurry was 150s, the foam air content was 62.78%, and the foam volume was 2868.10cm 3When 0.02 parts by weight of cellulose nanofiber whiskers were added, the half-life of the foam slurry was 136s, the foam air content was 63.23%, and the foam volume was 2880.96cm 3 When 0.02 parts by weight of carboxylated cellulose nanofibers were added, the foam slurry half-life was 209s, the foam air content was 64.40%, and the foam volume was 2996.73cm 3 ;Depend on Figure 7 It can be seen that the half-life: carboxylated cellulose nanofibers> sulfonated cellulose nanowhiskers> cellulose nanofiber whiskers> no nanoparticles; foam air content: no nanoparticles> carboxylated cellulose nanofibers> cellulose nanofiber whiskers> sulfonated cellulose nanowhiskers; foam volume: carboxylated cellulose nanofibers> no nanoparticles> cellulose nanofiber whiskers> sulfonated cellulose nanowhiskers. In general, carboxylated cellulose nanofibers can maintain better foam stability, while sulfonated cellulose nanowhiskers and cellulose nanofiber whiskers are not as good as carboxylated cellulose nanofibers in stabilizing foam.

[0083] Figure 8 is the comprehensive foam index diagram of different fibrous nanoparticle foaming agents. Figure 8 It can be seen that the foam comprehensive index of carboxylated cellulose nanofibers is the largest, which shows that carboxylated cellulose nanofibers are most beneficial to foam stability and can greatly improve the stability of foam. Compared with the addition of surfactants alone, the foam comprehensive index of sulfonated cellulose nanowhiskers and cellulose nanofiber whiskers does not increase much, which is beneficial to improving the stability of foam, but not as strong as carboxylated cellulose nanofibers.

[0084] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A method for preparing paper using a fiber-dispersed foaming agent for foam molding, characterized in that: The steps include: (1) Add 3-12 parts by weight of inorganic fiber, polyester fiber, and thickener to 700-800 parts by weight of water, and decompress. After decompressing, add 200-300 parts by weight of fiber dispersion foaming agent for foam molding, pre-stir and stir to obtain foam slurry; (2) pouring the foam slurry into a forming funnel, filtering to obtain a wet paper web, and drying to obtain finished paper; The fiber dispersion foaming agent for foam molding is composed of nanoparticles, surfactant and water, and the weight ratio of the nanoparticles, surfactant and water is (0.02-0.08): (0.4-6): 200; The nanoparticles are carboxylated cellulose nanofibers, and the diameter of the nanoparticles is 6-10 nm and the length is 2-3 μm.

2. The method for preparing paper using a fiber-dispersed foaming agent for foam molding according to claim 1, characterized in that: The surfactant is at least one of alkyl polyglucoside 0810, dodecyl trimethyl ammonium bromide, dodecyl dimethyl amine oxide and cocamidopropyl betaine.

3. The method for preparing paper by using a fiber-dispersed foaming agent for foam molding according to claim 1, characterized in that: The preparation method of the fiber-dispersed foaming agent for foam molding comprises the following steps: (1) Preparing nanoparticle dispersion: adding nanoparticles into water according to the formula, stirring, and ultrasonicating to obtain nanoparticle dispersion; (2) Preparation of fiber dispersing foaming agent: adding a surfactant to the dispersion prepared in step (1), stirring at a low speed, and ultrasonicating to obtain a fiber dispersing foaming agent.

4. The method for preparing paper by using a fiber-dispersed foaming agent for foam molding according to claim 3, characterized in that: The stirring in step (1) is first preliminary stirring, and then stirring at 20000-30000 rpm for 10-20 min; The ultrasonic time in steps (1) and (2) is 5-10 minutes.

5. The method for preparing paper by using a fiber-dispersed foaming agent for foam molding according to claim 1, characterized in that: The inorganic fiber is at least one of quartz fiber and alumina fiber, and has a length of 3-30 mm; The polyester fiber is at least one of PET fiber, PBT fiber and PTT fiber, and the amount used is 2-12 wt.% of the absolute dry inorganic fiber weight; The thickener is at least one of sodium alginate, sodium carboxymethyl cellulose, polyethylene oxide and sodium polyacrylate, and the amount used is 0.5-4.0 wt.% of the absolute dry inorganic fiber weight.

6. A paper product prepared by the method according to any one of claims 1 to 5.

Citation Information

Patent Citations

  • High-performance inorganic fiber preform as well as foam forming method and application thereof

    CN114717870A

  • Method of preparing fiber reinforced composite material through foam shaping method

    CN106948210A

  • Lignin fiber nano-fibril material, stable foam system based on material, preparation method of material, and preparation method and application of system

    CN109880118A

  • Cellulose nanocrystal reinforced foam system and preparation method thereof

    CN111560241A